PANDANGAN HUKUM ISLAM TERHADAP ADAT PEMBACAAN DO’A TOJOLOTA’ DI KECAMATAN CURIO KABUPATEN ENREKANG - Suharna (P3M STAI DDI Mangkoso, 2024)
The purpose of the research is to find out how the community views the traditional reading of the tojolota' prayer in Curio District, Enrekang Regency. The content is divided into three sub-discussions, namely: 1) The implementation of the custom of reading the tojolota prayer in the people of Curio District 2) Assessing the views of the people of Curio sub-district on the custom of reading prayers tojolota'? 3) Know the purpose of the people of Curio District, Enrekang Regency to maintain the custom of reading the tojolota prayer'? This type of research is qualitative research with the research approach used is: Empirical approach (syar'i) and the Socio-Legal approach in Curio District where the research takes place. The results achieved from this study are 1. In the implementation of the custom of reading the tojolota' prayer is not coercive for the people of Curio, if the family of the mayit is able to carry out it then it is fine, but if the family is unable then there is no coercion for them. 2. The Curio people's view of the custom of reading the do'a tojolota' is divided into two opinions, some say that it is haram and some say it is not haram. 3. The Curio community who still carries out the recitation of the tojolota' prayer has several objectives, namely with the aim of increasing friendship, because of social burdens and also because of fear of sin.